1997
DOI: 10.1055/s-2007-1015588
|View full text |Cite
|
Sign up to set email alerts
|

Sicherheit und Nutzen von Gadobutrol bei Patienten mit zerebralen Tumoren (Phase-III-Studie)

Abstract: For the differentiation of primary brain tumours the single dose was sufficient, in metastatic lesions triple dose was essential for the detection or exclusion of multifocality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
4
15
0
Order By: Relevance
“…was sufficient for differentiation of primary brain tumors in clinical practice, but a dose of 0.3 mmol/kg b.w. was essential for the detection or exclusion of multifocality for brain metastasis [21]. These data are confirmed by another clinical study with single-(0.1 mmol/kg b.w.)…”
Section: Mri Of Brain Tumorssupporting
confidence: 58%
See 1 more Smart Citation
“…was sufficient for differentiation of primary brain tumors in clinical practice, but a dose of 0.3 mmol/kg b.w. was essential for the detection or exclusion of multifocality for brain metastasis [21]. These data are confirmed by another clinical study with single-(0.1 mmol/kg b.w.)…”
Section: Mri Of Brain Tumorssupporting
confidence: 58%
“…on differentiation of primary brain tumors and detection rate of cerebral metastasis [21]. The authors concluded that a dose of 0.1 mmol/kg b.w.…”
Section: Mri Of Brain Tumorsmentioning
confidence: 99%
“…Gadobutrol and gadoterate have been successfully tested in both animal and human studies for safety and diagnostic reliability [8][9][10][11][12][13][14][15]. In Europe, gadobutrol is currently approved for contrast enhancement in cranial and spinal MRI, MR Angiography and MRI of the liver and kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…18 Higher dose administration is known to be more effective in lesion detection, but consideration must be given to reducing the amount of gadolinium administered to the patient because of the risk of contrast-related reactions and nephrogenic systemic fibrosis. 19,20 Gadobutrol had been proved to be a safe MR imaging contrast agent in patients with impaired renal function at doses of Յ0.3 mmol/L/kg of weight, 18 and no nephrogenic systemic fibrosis has been reported so far. 17 At this point, we can postulate that DD gadobutrol is expected to offer better opportunity for further improved enhancement than other Gd contrast agents because of the higher T1 relaxation effect.…”
mentioning
confidence: 99%